ROAD MAP FOR DEVELOPMENT OF PRICE REGULATION SYSTEM AND SYSTEM OF DRUG SUPPLY AT THE EXPENSE OF RUSSIAN FEDERATION HEALTHCARE SYSTEM FUNDS - M. V. Sura; K. V. Gerasimova; V. V. Omelyanovskiy; M. V. Avksentieva (Фармакоэкономика, 2015)
study goal is to prepare a road map for development of price regulation system and system of drug supply at the expense of funds of the healthcare system of the Russian Federation.Study methodology. A structured interview was conducted which involved 11 experts - key participants of the drug price regulation process in the Russian Federation in order to identify current problems and proposals on system reformation; there were analyzed manufacturer’s prices limits, prices of public drug supply contracts, prices for 25 drugs for treatment of malignant neoplasms and cardiovascular diseases, included in the list of vital and essential drugs (VED list) at Russian pharmacies; a road map for development of price regulation system and system of drug supply out of funds of the healthcare system of the Russian Federation for 2015-2017 was prepared.Study results. According to the participants of a structured interview which are the representatives of the Ministry of Health, pharmaceutical companies, distributors and pharmacy organizations,the existing system of drug price regulation requires significant legislative and structural changes aimed at transition from the system of state regulation of prices on drugs from the VED list to the system of public drug supply (comprehensive drug reimbursement system) and reference pricing. The analysis of prices on drugs from the VED list revealed significant (up to 25-fold) price differences for drugs within a single INN, one pack size and one dosage form based on the review of information from all sources.Conclusion. According to the prepared road map, the fundamental changes in the existing system of drug price regulation and public drug supply out of funds of the healthcare system of the Russian Federation shall include the following: transition from the price registration according to the trade names to the registration of drug prices according to international nonproprietary names (reference price) and promulgation of this system for all drugs purchased at public expense; negotiated pricing for drugs, which have no analogues; legislative regulation and introduction of co-payment of the population in case of expansion of public financing programs of drug supply. The initial steps in preparation for the reform of the system should be as follows: transition of the pharmaceutical manufacturers to compliance with the requirements of GMP standards; monitoring of quality, efficacy and safety of drugs circulating on the Russian market with further cancellation of drug registration in case of inefficacy; development of the list of interchangeable drugs and the list of drugs financed out of funds of the healthcare system; pilot implementation of reference pricing for drugs under the current drug reimbursement system.